Revitalizing Institutions to Enhance Climate Forecast Application in East Nusa Tenggara Province, Indonesia - Sahat M. Pasaribu (Analisis Kebijakan Pertanian, 2007)
Climate prediction is important in the overall development.NTTProvinceis considered as the area to which climate data and information are very critical. This region needs to optimize its programs to enhance climate forecast application for better regional development. The available climate information is not adequately used for early warning information for agricultural planning and development. The climate equipment and tools are owned and maintained by several institutions with the data used for their own purposes. This paper suggests that the quality of climate information is necessary to improve, so are the climate equipment and tools. The establishment of Climate Forum is required to revitalize related institutions dealing with climate information and to integrate various related resources for development.